Genetic variations in methotrexate metabolic pathway genes influence methotrexate responses in rheumatoid arthritis patients in Malaysia - Sha, Hong Xi; Veerapen, Kumar; Chow, Sook Khuan *; Gun, Suk Chyn; Lau, Ing Soo; Lim, Renee Lay Hong; Zaliha, Zulkifli; Yow, Yoon Yen *; Peh, Suat Cheng *; Hwang, Jung Shan * (Nature Publishing Group, 2022)
Methotrexate (MTX) is the most widely used disease-modifying anti-rheumatic drug (DMARD) for rheumatoid arthritis (RA). Many studies have attempted to understand the genetic risk factors that affect the therapeutic outcomes in RA patients treated with MTX. Unlike other studies that focus on the populations of Caucasians, Indian and east Asian countries, this study investigated the impacts of six single nucleotide polymorphisms (SNPs) that are hypothesized to affect the outcomes of MTX treatment in Malaysian RA patients. A total of 647 RA patients from three ethnicities (NMalay = 153; NChinese = 326; NIndian = 168) who received MTX monotherapy (minimum 15 mg per week) were sampled from three hospitals in Malaysia. SNPs were genotyped in patients using TaqMan real-time PCR assay. Data obtained were statistically analysed for the association between SNPs and MTX efficacy and toxicity. Analysis of all 647 RA patients indicated that none of the SNPs has influence on either MTX efficacy or MTX toxicity according to the Chi-square test and binary logistic regression. However, stratification by self-identified ancestries revealed that two out of six SNPs, ATIC C347G (rs2372536) (OR 0.5478, 95% CI 0.3396-0.8835, p = 0.01321) and ATIC T675C (rs4673993) (OR 0.5247, 95% CI 0.3248-0.8478, p = 0.008111), were significantly associated with MTX adequate response in RA patients with Malay ancestry (p < 0.05). As for the MTX toxicity, no significant association was identified for any SNPs selected in this study. Taken all together, ATIC C347G and ATIC T675C can be further evaluated on their impact in MTX efficacy using larger ancestry-specific cohort, and also incorporating high-order gene-gene and gene-environment interactions.